2003
DOI: 10.1001/archotol.129.5.523
|View full text |Cite
|
Sign up to set email alerts
|

Tracheotomy in Pediatric Patients

Abstract: Pediatric tracheotomy is associated with significant variation in rates and outcomes across the United States and across different hospital types. Further research to clarify the reasons for these associations is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
177
2
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 202 publications
(208 citation statements)
references
References 26 publications
27
177
2
2
Order By: Relevance
“…14,[18][19][20][21] The initiative to improve communication resulted in implementation of weekly clinical care conferences focused on treatment planning, with video review and discussion of airway pathology contributing an educational component. Efforts to avoid tracheostomy complications led to applying a consensus-driven algorithm to the decannulation process increasing the likelihood of successful decannulation by 18%, and aligning institutional standards with nationally recognized recommendations for interval airway surveillance examinations of 6 to 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…14,[18][19][20][21] The initiative to improve communication resulted in implementation of weekly clinical care conferences focused on treatment planning, with video review and discussion of airway pathology contributing an educational component. Efforts to avoid tracheostomy complications led to applying a consensus-driven algorithm to the decannulation process increasing the likelihood of successful decannulation by 18%, and aligning institutional standards with nationally recognized recommendations for interval airway surveillance examinations of 6 to 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that tracheostomy placement in the pediatric population is common, with approximately 5,000 procedures annually in the United States. 28 Graf et al 4 found that the most common reasons for tracheostomy placement in the pediatric population are airway management (63%), chronic respiratory disease (23%), central hypoventilation (9%), and neuromuscular weakness (6%). Other general indications include chronic respiratory disease, central hypoventilation syndrome, and neuromuscular weakness in descending order of occurrence.…”
Section: Tracheostomy Placement and Carementioning
confidence: 99%
“…HR ϭ hazard ratio CHD ϭ congenital heart disease NI ϭ neuromuscular impairment CAA ϭ congenital airway anomaly bation after cardiac surgery, 18,20,29,30 and comorbid chronic health conditions. 6,10 Although the effect was not significant, comorbidity with prematurity seemed to decrease the probability of tracheostomy placement (adjusted OR 0.89, 95% CI 0.58 -1.37), which may be due to the co-linearity between such factors as prematurity and chronic lung disease. Further investigations into the relationships between the severity of CHD, its management, and the effects of different comorbidities by age strata may clarify these uncertainties.…”
Section: Discussionmentioning
confidence: 92%
“…6,10,14 Reports have also indicated that the mortality rate among pediatric subjects with CHD and a tracheostomy ranges from 18.7% 6 to 52%. 20 In this study, we report a mortality rate of 43.1% for infants with CHD undergoing tracheostomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation